Analisis Reschedule Keterlambatan Proyek Reparasi Dua Kapal dengan Metode Critical Path Method (CPM) dan Time Cost Trade Off (TCTO) pada KM. Kendhaga Nusantara 4 dan TB. Sorowako Star - Syahada, Keisha Nandhini; Rindo, Good; Santosa, Ari Wibawa Budi; Prasetyo, Naufal Abdurahman (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2024)
The rescheduling due to delays in the repair project of two ships being worked on simultaneously was carried out using the Critical Path Method (CPM) and Time Cost Trade Off (TCTO). The data obtained came from the repair lists of each ship. The aim was to expedite project completion and achieve the most optimal time and cost efficiency. Acceleration alternatives were calculated, such as adding labor and extending work hours on the critical path. The acceleration steps included adding 2 and 4 extra working hours and increasing the number of workers. The analysis results showed that the most optimal time reduction was achieved by adding 4 hours of overtime and 21 additional workers, successfully reducing the project duration from 55 days to 20 days, with a time efficiency of 64% and a cost savings from Rp 393,300,000 to Rp 390,330,000, a savings of Rp 2,970,000 or around 0.7%. The daily productivity for scrapping work reached a maximum of 650 m²/day, while the increase in labor and 2 extra working hours resulted in 780 m²/day, and 4 extra working hours resulted in 845 m²/day.